2009
DOI: 10.3174/ajnr.a1425
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Citrullinated Myelin by1H-MR Spectroscopy in Early-Onset Multiple Sclerosis

Abstract: BACKGROUND AND PURPOSE:Myelin instability and citrullinated myelin basic protein have been demonstrated in the brains of patients with chronic and fulminating forms of multiple sclerosis (MS). Our aim was to trace citrulline in the brains of patients with early-onset MS by using proton MR spectroscopy ( 1 H-MR spectroscopy).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 24 publications
1
22
0
Order By: Relevance
“…Combining information across different imaging modalities is also important in order to understand further the relation between neuroinflammation and other well-documented abnormalities in brains of schizophrenia subjects, such as axonal pathology and oligodendroglia pathology (Najjar and Pearlman, 2015). Here, emerging technologies for the imaging of these additional pathologies (e.g., Oguz et al, 2009) show the most promise.…”
Section: Discussionmentioning
confidence: 99%
“…Combining information across different imaging modalities is also important in order to understand further the relation between neuroinflammation and other well-documented abnormalities in brains of schizophrenia subjects, such as axonal pathology and oligodendroglia pathology (Najjar and Pearlman, 2015). Here, emerging technologies for the imaging of these additional pathologies (e.g., Oguz et al, 2009) show the most promise.…”
Section: Discussionmentioning
confidence: 99%
“…Proton MR spectroscopy is a powerful imaging tool that has been used to assess a variety of intracranial pathological processes such as demyelinating lesions [7], tumours [8][9][10], multiple sclerosis [11,12] and Alzheimer's disease [13][14][15][16]. In order to detect early neurological changes in patients with ESRD, we evaluated the cerebral chemistry and metabolic changes by using proton MR spectroscopy.…”
Section: Discussionmentioning
confidence: 99%
“…The citrulline peak was found in NAWM, chronic and enhancing demyelinating lesions, but most frequently in NAWM with normal N-acetylaspartate/creatine [11]. Increased citrullination of myelin basic protein [MBP] diminishes its ability to organize lipid bilayers into compact multilayers, creates a more open structure to proteases such as cathepsin D, and thus results in myelin instability [21].…”
Section: Discussionmentioning
confidence: 99%
“…Some conventional (c) magnetic resonance (MR) studies found no difference with respect to lesion accumulation between EO and AO MS patients [4], while some others showed a gender predominancy and predilection of certain sites, such as the brain stem and deep gray matter, and more frequent occurrence of larger lesions in EO MS patients than the AO MS patients, which are considered bad prognostics in common AO MS [5][6][7][8]. Conflicting results of c MR studies led the investigators to assess microstructural changes in white and gray matter with and without demyelinating lesions on T2-weighted (W) imaging by advanced MR imaging techniques such as magnetization transfer imaging (MTI), proton ( 1 H) magnetic resonance spectroscopy (MRS) and diffusion tensor imaging (DTI) [9][10][11]. Among these, MTI, which provides an indirect in vivo measure of magnetization transfer between free and bound spins by using a saturation pulse, has a wide application in MS studies and has also shown subtle reductions in magnetization transfer consistent with macromolecular tissue damage in the brain parenchyma without observable lesions on T2-weighted (W) imaging, so-called 'normal appearing (NA) white and gray matter', even preceding lesion appearance [12].…”
Section: Introductionmentioning
confidence: 99%